ANALISA KEKUATAN TARIK DAN LENTUR KOMPOSIT BERPENGUAT SERAT DAUN NANAS (ANANAS COMOSUS) DENGAN KONFIGURASI CROSS-PLY LAMINATE - Aminur, Aminur; Sudarsono, Sudarsono; Bahar, Bahar (P3M Politeknik Negeri Indramayu, 2024)
Composite is a new type of material which is the result of engineering, consisting of two or more materials, with the properties of each material being different from each other both in terms of chemical and physical properties. The aim of this research is to determine the tensile and flexural strength values of pineapple leaf fiber composites with a cross-ply laminate configuration with fiber arrangement angles [0, 90°, 0°], [45˚, -45˚, 45˚] and [ 30°, -30°, 30°]. This research uses fiber arrangement directions [0, 90°, 0°], [45˚, -45˚, 45˚] and [30˚, -30 ˚, 30 ˚] with a cross-ply laminate configuration and uses. The composite was made in a composite mold measuring P = 190 mm, L = 90 mm and t = 5 mm. The results of this research show that the influence of the pineapple leaf fiber orientation angle on the average tensile stress value of composites with pineapple leaf fiber cross-ply laminate configuration with the highest tensile stress value is shown by the fiber direction at an angle of [30°, -30°, 30°] amounted to 27,611 MPa, while the lowest composite value with the angle [45˚, -45˚, 45˚] was 19,407 MPa. The highest bending stress value is found in the composite with an orientation angle of [0, 90°, 0°] with an average value of 59.002 MPa, while the composite with a fiber orientation angle of [45˚, -45˚, 45˚] has a higher bending stress value. low at 32.974 MPa.